Identification of a PANoptosis-related gene signature reveals therapeutic potential of SFRP2 in pulmonary arterial hypertension - Li, Li; Juaiti, Mukamengjiang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPulmonary arterial hypertension (PAH) is a serious condition marked by elevated pulmonary artery pressure, often progressing to right heart failure and high mortality. PANoptosis, an inflammatory form of programmed cell death, remains understudied in the context of PAH. This study aims to identify and validate PANoptosis-related signature genes in PAH using bioinformatics analysis alongside in vivo and in vitro experiments, seeking to uncover its potential role in disease progression.MethodsPAH-related datasets and PANoptosis-associated genes were sourced from the Gene Expression Omnibus (GEO) database and prior studies. Feature genes were identified through weighted gene co-expression network analysis (WGCNA), least absolute shrinkage and selection operator (LASSO), and random forest (RF) algorithms, with validation performed on external datasets. The immune landscape in PAH was characterized using the CIBERSORT algorithm, providing insights into immune cell composition and its role in disease progression. Gene expression was further validated using a rat PAH model and pulmonary artery fibroblasts (PAAFs), while hub gene functions were investigated at the cellular level through Western blot, CCK-8, and flow cytometry assays.ResultsThrough integrated transcriptomic analysis, SFRP2 was identified as a feature gene related to PAH and PANoptosis. Experimental validation was conducted in MCT-induced rat PAH models and TGF-β1-induced PAAFs, confirming SFRP2's role in regulating fibroblast proliferation and anti-apoptotic processes. The diagnostic model derived from dataset analysis exhibited high accuracy in diagnosing PAH, while immune cell infiltration analysis highlighted immune dysregulation associated with the condition.ConclusionSFRP2 was identified as a potential biomarker for PAH, impacting cell proliferation and resistance to apoptosis, thus providing new insights for PAH prevention and treatment.